A letra e o espírito da lei - Fernandes, Darley Alves (2019)
In the current dissertation, we discuss the way that the norms and the moral principles objectively justified by the reason can become subjective grounds of determination of the will (motive). Taking into account that the moral norms are normative principles that affirm something about us, telling us what to do and claiming that we must to do so, our thesis is that we only can understand the motivational character of the moral norms through the "moral consciousness". The consciousness of duty is the conscience of being submitted to a moral obligation that is valid for me because it is inevitable to me, once I recognize my "reasons for acting" through it. From this premise we can defend that: (i) there is just a formal distinction between the objective grounds and the subjective grounds so that the "objective grounds" are "motives"; (ii) the subjective validity of these norms it is not independent on the subject who judges and is submitted to them. Therefore, we cannot understand the motivational character of the reason without comprehending its normativity, once both are capabilities that form what we call "practical reason". Then, to talk about the motivational ability of the practical reason is to talk of its normativity and vice-versa, it is because of that the moral consciousness purchase central relevance in our investigation, once it reveals these two virtues of the practical reason. Insofar this fundamental consciousness of the "law of duty" is presented as a "fact of reason", it is the highest point of Kantian moral philosophy. Exploring the fundamental consciousness of the law we are affirming that the condition of the subjective validity of the norms and moral principles is the own "immanence" of these principles, this immanence is revealed by the consciousness.